2022
DOI: 10.3390/universe8010054
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Production of Phosphine by Venusian Volcanoes

Abstract: The initial reports of the presence of phosphine in the cloud decks of Venus have led to the suggestion that volcanism is the source of phosphine, through volcanic phosphides ejected into the clouds. Here, we examine the idea that mantle plume volcanism, bringing material from the deep mantle to the surface, could generate observed amounts of phosphine through the interaction of explosively erupted phosphide with sulfuric acid clouds. The direct eruption of deep mantle phosphide is unphysical, but a shallower … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 101 publications
(155 reference statements)
0
12
0
Order By: Relevance
“…The origins of any phosphine present are also debated, and most scenarios are hard to test for lack of some contextual data. For example, it seems only extreme volcanic activity could make ~ppb-level phosphine (Bains et al, 2022) but vulcanism on Venus is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…The origins of any phosphine present are also debated, and most scenarios are hard to test for lack of some contextual data. For example, it seems only extreme volcanic activity could make ~ppb-level phosphine (Bains et al, 2022) but vulcanism on Venus is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Such an analysis was conducted in [58] where a wide range of chemical processes were examined to see if there is any potential source of phosphine in sufficient abundance to explain the observations with processes that we know are underway on the planet. The processes examined included gas reactions, geochemical reactions, photochemistry, volcanism (see also [59]), lightning and impactors. An example of the kind of chemical reaction network considered is shown in Figure 11, where the reaction rate and the destruction rates are compared.…”
Section: The (Im)possible Origins Of Phosphine On Venusmentioning
confidence: 99%
“…For phosphine to be produced in significant amounts the whole reaction network must have this ratio ≥ 1 but, as can be seen, critical segments of the network have ratios orders of magnitudes less than this. More generally, it was found that the lifetime of free phosphine at various altitudes in the atmosphere of Venus ranged from < 1 second to perhaps a century [59], making it highly unlikely that a significant amount of phosphine can accumulate from any hypothetical source.…”
Section: The (Im)possible Origins Of Phosphine On Venusmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there have been some attempts to explain the presence of PH 3 on Venus through known abiotic chemistry [42,43]. So far, however, none of these attempts have been able to satisfactorily explain the presence of PH 3 , either because they do not predict enough PH 3 to explain the observations, especially above the clouds, or because they predict other molecules, especially water vapor, in large amounts that contradict observations [30,44,45]. Life using expected energy-metabolic pathways produce similar contradictions [46].…”
Section: Phosphinementioning
confidence: 99%